2020
DOI: 10.1038/s41467-020-15497-1
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic KrasG12D causes myeloproliferation via NLRP3 inflammasome activation

Abstract: Oncogenic Ras mutations occur in various leukemias. It was unclear if, besides the direct transforming effect via constant RAS/MEK/ERK signaling, an inflammation-related effect of KRAS contributes to the disease. Here, we identify a functional link between oncogenic Kras G12D and NLRP3 inflammasome activation in murine and human cells. Mice expressing active Kras G12D in the hematopoietic system developed myeloproliferation and cytopenia, which is reversed in Kras G12D mice lacking NLRP3 in the hematopoietic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 109 publications
(101 citation statements)
references
References 39 publications
4
97
0
Order By: Relevance
“…These phenotypes are often seen in chronic myelomonocytic leukemia (CMML), juvenile myelomonocytic leukemia (JMML) and more rarely acute myeloid leukemia (AML) patients harboring KRAS mutations. Additionally, we found evidence of NLRP3 inflammasome activation upon analyzing JMML, CMML, and AML patient samples harboring KRAS mutations, providing a stronger evidence of the participation of NLRP3 inflammasome in the disease development ( 49 ). An open question remains how the NLRP3 inflammasome activation drives hematological malignancies, whether by a cell-autonomous signal that promotes cell proliferation directly or via a modification of the TME or both.…”
Section: Nlrp3 Inflammasomementioning
confidence: 70%
“…These phenotypes are often seen in chronic myelomonocytic leukemia (CMML), juvenile myelomonocytic leukemia (JMML) and more rarely acute myeloid leukemia (AML) patients harboring KRAS mutations. Additionally, we found evidence of NLRP3 inflammasome activation upon analyzing JMML, CMML, and AML patient samples harboring KRAS mutations, providing a stronger evidence of the participation of NLRP3 inflammasome in the disease development ( 49 ). An open question remains how the NLRP3 inflammasome activation drives hematological malignancies, whether by a cell-autonomous signal that promotes cell proliferation directly or via a modification of the TME or both.…”
Section: Nlrp3 Inflammasomementioning
confidence: 70%
“…In addition, the pharmacological inhibition of either NLRP3 or IL-1R led to an improvement of the disease phenotypes caused by the KRAS mutation. These findings in mice were reproduced in human chronic myelomonocytic leukaemia (CMML), juvenile myelomonocytic leukaemia (JMML) and acute myeloid leukaemia (AML) harbouring KRAS mutations 55 . Altogether, several lines of evidence have emerged supporting the pro-tumourigenic role of NLRP3 inflammasome in cancer.…”
Section: Kras-induced Inflammationmentioning
confidence: 81%
“…Mechanistically, the groups showed an association of the PD-L1/NLRP3 inflammasome pathway to the recruitment of MDSCs into the tumour tissue causing impairment of the anti-tumour response 54 . Nevertheless, there was no direct link between KRAS mutations and the NLRP3 inflammasome until we recently reported that oncogenic KRAS causes the activation of NLRP3 inflammasome, which has roles in the pathogenesis of KRAS-driven myeloproliferation 55 . Using genetic mouse models as well as patient samples, we observed that the NLRP3 inflammasome had a key role in the development of several features of KRAS-mutant myeloid leukaemia including cytopenia, splenomegaly and myeloproliferation.…”
Section: Kras-induced Inflammationmentioning
confidence: 99%
“…5). A proinflammatory status, with high levels of cytokines, such as IL-1β, TNF-α, GM-CFS, has been previously assigned to JMML in human patients and mouse models, and shown to be generated by myeloid cells (Bagby et al, 1988;Dong et al, 2016;Freedman et al, 1992;Hamarsheh et al, 2020;Zhao et al, 2018). The inflammatory response may be initiated in a cell autonomous way or in response to signals from the microenvironment.…”
Section: Discussionmentioning
confidence: 99%